Foul perfection : essays and criticism - Kelley, Mike; Welchman, John C. (Cambridge, Mass. : MIT Press, 2003)
The work of artist Mike Kelley embraces performance, installation, drawing, painting, video, and sculpture. Drawing distinctively on high art and vernacular traditions, including historical research, popular culture, and psychology, Kelley came to preminence in the 1980s with a series of sculptures composed of craft materials. His recent work offers dialogues with architecture and with repressed memory syndrome, and a susatined inquiry into his own aesthetic and social history. The subjects on which Kelley has written are as varied as his artistic media; They include the work of fellow artists, sound, caricature, the uncannyn UFOlogy, and gender-bending.
This book offers a diverse collection of Kelley's writings from the last twenty-five years. It features major critical texts on art, film and the wider culture, including his piece on the aesthetic he calls "urban Gothic". It also contains essays, mostly commissioned for exhibition catalogs and journals, on the artists and groups David Askevold, Öyvind Fahlström, Douglas Huebler, John miller, Survival Research Laboratories, and Paul Thek, among others. Kelley's voices are passionate, analytic, and ironic, and his critical intelligence is leavened with touches of whimsy.
Includes bibliographical references and index.
boek
Keywords: Kelley, Mike